2022
DOI: 10.1007/s10896-022-00395-5
|View full text |Cite|
|
Sign up to set email alerts
|

Substance Use and Intimate Partner Abuse (IPA): A Descriptive Model of the Pathways Between Substance Use and IPA Perpetration for Men

Abstract: Intimate partner abuse (IPA) is a pervasive public health and human rights issue disproportionately affecting women. There is a complex link between IPA and substance use; substance use can increase both the frequency and severity of IPA. Pathway models have been applied to explore heterogeneous trajectories into other behaviours and to identify areas for intervention. This approach has not previously been applied in the area of substance use and IPA. Inductive thematic analysis of 37 interviews with heterosex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Other salient, identified risk factors in IPV perpetrators with ADUPs were, in terms of personality disorders, a trend towards higher scores on antisocial and borderline personality disorders, in terms of clinical symptomatology, higher clinical symptomatology, depression, and trauma symptomatology and, in terms of executive functions, higher mental rigidity. According to Gilchrist et al (2022) , one of the pathways into substance use-related IPV revealed that perpetrators reported using substances as a coping mechanism to help them deal with their emotional pain and mental health issues caused by unresolved previous trauma. Similarly, the self-medication hypothesis states that individuals with PTSD are more likely to develop ADUPs in light of a tendency to drink or use drugs to alleviate PTSD symptoms and cope with difficult internal experiences ( Hawn et al, 2020 ; Khantzian, 1997 ; Lawrence et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other salient, identified risk factors in IPV perpetrators with ADUPs were, in terms of personality disorders, a trend towards higher scores on antisocial and borderline personality disorders, in terms of clinical symptomatology, higher clinical symptomatology, depression, and trauma symptomatology and, in terms of executive functions, higher mental rigidity. According to Gilchrist et al (2022) , one of the pathways into substance use-related IPV revealed that perpetrators reported using substances as a coping mechanism to help them deal with their emotional pain and mental health issues caused by unresolved previous trauma. Similarly, the self-medication hypothesis states that individuals with PTSD are more likely to develop ADUPs in light of a tendency to drink or use drugs to alleviate PTSD symptoms and cope with difficult internal experiences ( Hawn et al, 2020 ; Khantzian, 1997 ; Lawrence et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the need to address the function of substance use in intervention programs for IPV perpetrators with ADUPs. Effective interventions with this high-risk group of perpetrators should focus on re-scripting childhood experiences, reframing unhelpful schemas, and expressing emotional needs to enhance self-regulation and trauma healing ( Gilchrist et al, 2022 ). However, as IPV perpetrators with ADUPs present high dropout and recidivism rates, retention strategies are also needed to help them complete the intervention and improve their outcomes ( Lila et al, 2020 ; Olver et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed the ADVANCE perpetrator group program (25)(26)(27) to address the complex interplay between substance use and IPV perpetration in the context of intoxication, withdrawal, craving and acquiring substances (28)(29)(30), neglected in other programs. Our research highlighted the importance of addressing sexual jealousy and entitlement, the wider dynamics of power and control, and psychological vulnerabilities (29)(30)(31).…”
Section: Introductionmentioning
confidence: 95%